PENGARUH TINGKAT PEMAHAMAN DAN MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGAMBIL PROFESI CHARTERED ACCOUNTANT (CA) PADA UNIVERSITAS ISLAM SWASTA DI KOTA MEDAN - Sayyidatun Nisa (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2019)
This  study  aims  to   examine  and   analyze  the   influence  of   the   level  of understanding of Chartered Accountant (CA), motivation to obtain  a Chartered Accountant (CA) and  attitudes regarding Chartered Accountant (CA) on  the interest of students to  take  up  the  profession Chartered Accountant (CA) at Private  Islamic Universities in Medan  City. This research uses the  associative quantitative research. This study uses  primary  data where  data is collected using a questionnaire. This research was conducted on the  seventh semester students of class 2015  at the  Private  Islamic University in Medan  City with a population of 747  students and  a sample of 261  respondents. Data  analysis techniques in this study used descriptive statistics, classic assumption tests, multiple linear regression analysis, hypothesis testing and coeficient of determination tests. The results of the analysis show that  the level of understanding of Chartered Accountant (CA) affects the interest of students to take  the chartered accountant profession. Motivation  to get a Chartered Accountant  (CA)  affects  the   interest  of  students  to   take   the   chartered accountant profession. The attitude about Chartered Accountant (CA) affects the  interest  of  students to  take   the  chartered accountant  profession.  The results of the analysis prove that  simultaneously the Level of Understanding of Chartered Accountant (CA), motivation to get a Chartered Accountant (CA) and attitudes  regarding  Chartered  Accountant  (CA)  influence  the   interest  of students to take the chartered accountant profession.